Apakah Model Pembelajaran Reciprocal Teaching dapat Meningkatkan Minat Belajar dan Hasil Belajar Biologi Siswa SMA? (Does Reciprocal Teaching Learning Model can Increase Learning Interest and Biology Learning Outcomes of High School Students) - Shefa Dwijayanti Ramadani; Mas’udhatul Qibtiyah (BIODIK, 2021)
This study aims to investigate the effect of the Reciprocal Teaching (RT) learning model on learning interest and biology learning outcomes of high school students. This research was conducted through a quasi-experimental design with a pretest-posttest control group design. This study involved students of tenth grade of MA Miftahul Ulum Bettet Pamekasan. Two classes were taken randomly each to be applied RT learning model and conventional learning. Student’s learning interest data were collected through the distribution of questionnaires; while learning outcomes were measured through essay tests. The data obtained were then analyzed using ANACOVA test with a significance level of 0.05. The results showed that RT could increase student’s learning interest (p = 0.034) and student’s learning outcomes (p = 0.000). Thus, RT can be used as alternative learning model for teachers to empower students' learning interest and learning outcomes. Abstrak. Penelitian ini Bertujuan untuk menyelidiki pengaruh model pembelajaran Reciprocal Teaching (RT) terhadap minat belajar dan hasil belajar Biologi siswa SMA. Penelitian dilaksanakan melalui desain quasi eksperimen dengan rancangan pretest-posttest control group design. Penelitian melibatkan siswa kelas X MA Miftahul Ulum Bettet Pamekasan. Dua kelas diambil secara acak masing-masing untuk diterapkan model pembelajaran RT dan pembelajaran konvensional. Data minat belajar siswa dikumpulkan melalui penyebaran angket; sementara hasil belajar diukur melalui tes essai. Data yang diperoleh selanjutnya dianalisis menggunakan uji ANACOVA dengan nilai signifikansi sebesar 0,05. Hasil penelitian menunjukkan bahwa RT dapat meningkatkan minat belajar (p = 0,034) dan hasil belajar siswa (p = 0,000). Dengan demikian, RT dapat digunakan sebagai alternatif pembelajaran bagi guru untuk memberdayakan minat sekaligus hasil belajar siswa.